Principais aspectos cirúrgicos da urolitíase em cães - Tanaka, Aline Shioya [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Urolithiasis occurs with relatively frequency among the diseases that affect the urinary tract of dogs. It`s fundamental that samples of the uroliths are sent for analysis, because, in agreement with the mineral composition of the urolith and also its location, the choice is made between the surgical treatment or the clinical dissolution. Cystotomy is the surgical technique more accomplished in the bladder of small animals, due to its simplicity, when in comparison with other procedures for removal of calculi. With the aid of lithotripsy and endoscopy, the surgical interventions in the urinary treatment tend to be less and less invasive, minimizing the risks of subsequent complications. Chances of recurrence of the urolithiasis are usually larger in patients submitted to the surgical intervention. Besides, the time elapsed among regressive episodes is larger after the clinical dissolution

A urolitíase ocorre com relativa freqüência dentre as afecções que acometem o trato urinário de cães. É fundamental que amostras dos cálculos sejam enviadas para análise, visto que, de acordo com a composição mineral do urólito e também sua localização, tem-se a escolha entre o tratamento cirúrgico ou a dissolução clínica. A cistotomia compreende a técnica cirúrgica mais realizada na bexiga dos pequenos animais, devido à sua simplicidade, quando em comparação aos demais procedimentos para remoção de cálculos. Com o auxílio da litotripsia e endoscopia, as intervenções cirúrgicas no trato urinário tendem a ser cada vez menos invasivas, minimizando os riscos de complicações posteriores. As chances de recidiva da urolitíase geralmente são maiores em pacientes submetidos à intervenção cirúrgica. Além disto, o tempo transcorrido entre episódios recidivantes é maior após a dissolução clínica
Keywords: Cão – Cirurgia; Aparelho urinário – Cálculos - Cirurgia